Frequency of New Onset Atrial Fibrillation in Acute Myocardial Infarction Patients with high CHADS2 Score - Dar, Muhammad Habeel; -, Sohail; Adnan, Yasir; Noor, Lubna; Hafizullah, MohammadMohammad Hafizullah (International Journal of Pathology, 2018)
Objectives: This study was designed to find out the Frequency of new onset atrial fibrillation in patients with acute myocardial infarction having HIGH CHADS2 SCORE.Material and Methods: This was a Cross Sectional Descriptive study. The study was carried out at the Department of Cardiology, Lady Reading Hospital Peshawar From 7th March to 6th September 2014. All Patients with acute myocardial infarction having CHADS2 SCORE 3 and above were enrolled. Patients were monitored for AF during their total hospital stay. Study end point was new onset atrial fibrillation that last for more than 30 seconds. Data analysis was done using SPSS version 16.Results: We enrolled 186 patients of acute myocardial infarction patients having CHADS2 SCORE three or more at admission. The mean age was 56.55 years + 13.992SD years. Out of 186, 99(53.23%) were male and 87(46.77%) were female patients. Over all new onset atrial fibrillation was observed in 40(21.51%) patients having acute myocardial infarction patients with High CHADS2 SCORE while 146(78.49%) have not faced the new onset atrial fibrillation during the study period. About 20(23%) female patients presented with acute myocardial infarction patients having High CHADS2 SCORE, developed new onset atrial fibrillation as compared to 20(20.2%) male patients who developed new onset atrial fibrillation. However, this difference was statistically not significant.Conclusion: Atrial fibrillation is one of the most common heart rhythm disorders, with a prevalence that is on the rise. Risk factors for the development of AF are very similar to those for developing coronary artery disease. AF is often associated with acute myocardial infarction in patients with High CHADS2 SCORE. Emphasis should be given on prevention, early detection and immediate management of atrial fibrillation in patients of acute myocardial infarction having High CHADS2 SCORE.